Clinical characteristics and degree of cardiovascular risk factor control in patients with newly-diagnosed type 2 diabetes in Catalonia - Ramírez-Morros, Anna; Franch-Nadal, Josep; Real, Jordi; Miró-Catalina, Queralt; Bundó, Magdalena; Vlacho, Bogdan; Mauricio, Didac (Frontiers in Endocrinology, 2024)
Women with type 2 diabetes mellitus (T2DM) face a greater risk of cardiovascular disease (CVD) and encounter challenges in managing cardiovascular risk factors (CVRF); however, limited data are available in individuals with newly-diagnosed T2DM. This study aimed to examine differences between women and men at the onset of T2DM in terms of clinical characteristics, glycaemic status, and CVRF management. This was a retrospective cohort study including 13,629 subjects with newlydiagnosed T2DM from the System for the Development of Research in Primary Care (SIDIAP) database in Catalonia (Spain). Sex differences (Dif) were assessed at baseline and 1-year postdiagnosis, by calculating the absolute difference of means or proportions. Women were older and had a higher BMI than men. At baseline, women had higher total cholesterol [Dif (95%CI) 10 mg/dL (9.1/10.8)] and low-density lipoprotein cholesterol (LDL-c) [Dif (95%CI) 7 mg/dL (6.3/7.7)], while men had higher rates of smoking and alcohol intake. Lipid target achievement was lower in women, in both primary prevention (LDL-c < 100 mg/dL) [Dif (95%CI) -7.3 mg/dL (-10.5/-4.1)] and secondary prevention (LDL-c < 70 mg/dL) [Dif (95%CI) -8.3 mg/dL (-17.3/0.7)], along with lower statin and antiplatelet prescriptions, especially one year after diagnosis. Changes in clinical and laboratory data one year post-diagnosis revealed that, in the primary prevention group, men experienced greater improvements in total cholesterol, LDL-c and triglycerides, while women had less success in achieving CVRF control targets compared to men. Additionally, cardiovascular events, such as coronary artery disease and peripheral artery disease increased more in men than in women within the first year of diagnosis, especially in primary prevention subjects. In conclusion, differences between men and women CVRF are already apparent at the onset of T2DM, particularly in primary prevention, with notable differences in lipid profile and target level attainment.